Cross-sectional study of hepatitis E virus (HEV) circulation in Italian pig farms - Ianiro, Giovanni; Pavoni, Enrico; Aprea, Giuseppe; Romantini, Romina; Alborali, Giovanni Loris; D'Angelantonio, Daniela; Garofolo, Giuliano; Scattolini, Silvia; De Sabato, Luca; Magistrali, Chiara Francesca; Burow, Elke; Ostanello, Fabio; et al. (Frontiers in Veterinary Science, 2023)
Foodborne transmission is considered the main way of spreading zoonotic hepatitis E virus (HEV) infection in Europe. In recent years, the human cases of hepatitis E in subjects without history of travel in endemic areas have increased, suggesting that domestic HEV transmission is increasing. Pork products with or without liver, are often indicated as the source of many human foodborne HEV cases as well as small outbreaks. Pigs are recognized as the main reservoir of the zoonotic HEV-3 genotype, the most frequently detected in human cases in the EU. In the absence of a harmonized surveillance of HEV circulation, data on prevalence are heterogeneous but confirm a widespread circulation of HEV-3 in pig herds across EU. HEV-3 can pass through the food chain from farm to fork when infected animals are slaughtered. In Italy, several studies reported the circulation of HEV-3 in pig farms, but results are heterogeneous due to different methodologies applied. In the present study, we performed a survey over 51 pig herds belonging to three main types of farms: breeding, fattening and farrow-to-finish. HEV-RNA was analysed by broad range Real-time RT-PCR on 20 samples for each farm, obtained by pooling together feces from 10 individuals. Overall, HEV RNA was confirmed on 150 fecal pooled samples out of 1,032 (14.5%). At least one positive pooled sample was detected from 18 farms out of 51 tested (35.3%). By lowering the number of infected pigs at primary production, the risk of HEV-3 entering into the food chain can be reduced. Hence, information on HEV circulation in herds is highly relevant for choosing preventive measures and deserves development of a monitoring program and further investigations.